An Application of Problem-Solving Based Student Facilitating and Explaining Teaching Model to Improve Students' Metacognitive Ability - Anggraeni, Yusida; Listiaji, Prasetyo (Jurnal Inovasi Pendidikan IPA, 2024)
This research aims to reveal (1) the impact of implementing the student facilitating-and-explaining teaching model based on problem-solving on the improvement of students' metacognitive abilities, (2) the profile of metacognitive abilities, and (3) students' responses. This research is a quasi-experiment with a nonequivalent control group design. The sample was established using the simple random sampling technique, resulting in one control group and one experimental group. Research data were obtained from pretest and posttest scores of metacognitive abilities, the MAI self-assessment questionnaire, and students' response questionnaires. The t-test results show that the tcount is higher than ttable, indicating a significant difference between the post-test scores of the experimental and control groups. Additionally, the profile of students' metacognitive abilities before the learning process was mostly in the low and sufficient criteria, while after the implementation of the learning model, metacognitive abilities were mostly in the good criteria. The research findings were also supported by students' response questionnaire, with an 80.66% rating in the good category. In conclusion, the student facilitator and explaining model based on problem-solving have a significant impact on the improvement of students' metacognitive abilities.